Segurança do alimento e segurança alimentar: uma análise a partir da agroindústria familiar de derivados de leite na microrregião de Itapetininga – SP - Granato, Leticia Senteio Silles (Universidade Federal de São Carlos, 2022)
This research analyzes the production of dairy products by family farmers in the Microregion of Itapetininga - SP, and aims to provide a Food Safety Indicator (ISA) derived from dairy products and the safety grau to feed families by means of the Brazilian Food Safety Scale. Feed (EBIA). We applied semi-structured questionnaires in interviews with ten family farmers in two municipalities of Angatuba, Buri, Campina do Monte Alegre and Itapetininga. Both indicators are categorized according to the levels observed, and other productive and socioeconomic variables obtained during the field investigations are also presented. The results indicate insufficient levels of hygienic-sanitary safety and oil derivatives, demonstrated by ISA. Despite this, the levels of marketing of the products are available to the families of family farmers who are not affected. Likewise, through the analysis of the EBIA indicator, it was possible to observe that the families studied were in conditions of food security.
Food safety and food safety: an analysis from the family agroindustry of dairy derivatives in the Itapetininga microregion – SP
Keywords: Segurança alimentar; Segurança do alimento; Agroindústria familiar; Produtos lácteos; Food security; Food safety; Small dairy farms; Dairy products; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL